Pengaruh Fasilitas Kerja Terhadap Kepuasan Karyawan Di Imelda Hotel-Waterpark-Convention Padang - Nova Shabrina; Ira Meirina Chair (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
The This study aims to determine the Effect of Working Facilities on Employee satisfaction at Imelda Hotel-Waterpark-Convention Padang. This type of research is classified into quantitative descriptive research with causative associative methods.1The population in this study were all employees who worked at Imelda Hotel-Waterpark-Convention Padang as many as 72 people using saturated sampling techniques. Data collection techniques usingma questionnaire with a Likert scale that has been tested for validity and reliability. Data were analyzed through description analysis and simple linear regression test and coefficient of determination with the help of SPSS Computer Program version 16.00. The results of the study show that: Work Facilities in the category of Good have a percentage of 51.39% and Satisfaction of employees with the category of Good has a percentage of 86.11%. Furthermore, the R Square value is 0.094 with the level of sig. 0.009 <0.05, the Work Facility variabledcan explain the variable Employee Satisfaction of 9.4% and 90.6% influenced by other factors.